Diferencias en el Control Metabólico entre Adolescentes y Adultos con Diabetes Mellitus Tipo 1 en el Hospital San Juan De Dios, de Marzo a Agosto 2007 - Aguilar Valdés, Abner (2012)
Background: Debut and/or progression of type 1 diabetes mellitus often occurs during adoles- cence, a stage characterized by the desire for independence and sometimes risky behaviors. The aim of the study was to compare glycemic control and epidemiology in adolescents and adults with type 1-Diabetes. Methods: We per- formed an observational cross-sectional study with 99 type 1 diabetics, assessing variables of medical history, laboratory results (glycemic control, urinary albumin excretion, lipid profile) and chronic micro and macrovascular complica- tions. Adolescents were defined as subjects aged 18 years or less and adults, subjects over 18. We performed a comparative analysis of the varia- bles between the adolescent group (n=34) and adult group (n=65) of the study. Results: The average age of the subjects was 25.0 ± 9.9 years, with an average duration of diabetes of 12.8 ± 8.6 years. There were statistically significant differences between adolescents and adults with type 1 diabetes in the following variables: age at diagnosis (P=0.005), baseline age (P=0.002), body mass index (P<0.001), presence of dyslipidemia (P<0.001), diabetic retinopathy (P=0.018) and diabetic nephropathy (P=0.001), insulin requirements (P=0.041), use of ACE inhibitors (P=0.001) and statins (P<0.001), HbA1c levels (P=0.009) and triglycerides (P=0.038). The average glycemic control was significantly worse in the adolescent group (HbA1c = 9.35 ± 2.26%) compared with adults (HbA1c = 8.23 ± 1.81%), however, this did not translate into increased prevalence of chronic complications at the time when analysis was made. Conclusions: Adolescence can exert a significant and deleterious effect on the metabol- ic control of type 1 diabetes mellitus compared with the adult stage of life.